2008
DOI: 10.1196/annals.1428.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Therapeutic Efficacy between Ivermectin, Selamectin, and Moxidectin in Canaries during Natural Infection with Dermanyssus gallinae

Abstract: The aim of this study was to compare the efficacy of three spot-on drugs on canaries during Dermanyssus gallinae natural infections and during the breeding season. Three groups of canary couples (seven couples each) were included: group A was treated with ivermectin, B with selamectin, and C with moxidectin. All the drugs were administered topically infrascapularly. The parasitic charge was estimated before the treatment (t(0)) and after 8 (t(1)), 16 (t(2)), 24 (t(3)), and 32 (t(4)) days following the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For example, it was found that the intra-abdominal injection of birds with ivermectin at 0.6 mg/kg was insufficient to control D. gallinae and efficacious concentrations were from 1.8 to 5.4 mg/kg [30, 31]. In addition, after the initial treatment, ivermectin and selamectin were most efficacious against D. gallinae on Day 16, and moxidectin was most effective in control of mites on Day 24 [32]. Compared with intraperitoneal injection or subcutaneous administration, oral administration is more convenient to birds (particularly for a large number of birds on poultry farms).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that the intra-abdominal injection of birds with ivermectin at 0.6 mg/kg was insufficient to control D. gallinae and efficacious concentrations were from 1.8 to 5.4 mg/kg [30, 31]. In addition, after the initial treatment, ivermectin and selamectin were most efficacious against D. gallinae on Day 16, and moxidectin was most effective in control of mites on Day 24 [32]. Compared with intraperitoneal injection or subcutaneous administration, oral administration is more convenient to birds (particularly for a large number of birds on poultry farms).…”
Section: Introductionmentioning
confidence: 99%
“…This compoundwhen administered in waterwas effective in removing Ascaris galli, Heterakis gallinarum and Capillaria spp. in poultry (Schepkins et al 1985;Sharma et al 1990;Todisco et al 2008;Khayatnouri et al 2011). It is a very lipophilic molecule, so residues remain for long periods in the treated animal tissues, especially those with a high fat content (Baynes et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…IVM is reported to be effective against nematode infections in poultry, but it is not approved for use in avian species. IVM administered in water was effective in removing Ascaris galli, Heterakis gallinarum, and Capillaria in poultry. The available data describing the pharmacokinetic behavior of IVM in avian species is scarce. In some countries, until recently there were some oral formulations to control internal and external parasites in pet or game birds and fighting cocks, but most of them are no longer on the market.…”
Section: Introductionmentioning
confidence: 99%